Pengembangan Model Kontribusi Network Governance dalam Value Chain untuk Meningkatkan Keunggulan Bersaing Usaha Perikanan Tangkap - Imas Soemaryani; Ernie Tisnawati; Deki Fermansyah (Jurnal Bisnis Manajemen, 2015)
With 81,000 km long coast, Indonesia has the marine economy potential equivalent to 12,000 trillion. Java and Bali is the largest producer of capture fisheries in Indonesia, and West Java ranks second largest fisheries production in Java island Java, and in West Java itself, Indaramayu District has the largest potential for marine fish. With this the largest production potential, Indramayu district should be able to increase the welfare of fishermen, but due to the sales chain system fishermen catch less in favor of the fishermen, the fishermen in Indramayu not have a competitive advantage in running their fisheries activities. This study aims to analyze the implementation of network governance in the ecosystem, at harvest, during the production process and product to the consumer. Thus the unit of analysis in this study were fishermen, wholesalers (collector), retailers and other institutions associated with network governance in Indramayu. The method used is an explanatory survey and focus group discussions. This research resulted in a contribution to the development of network governance models in the value chain to increase competitive advantage to fishing in Indramayu.